Demographic and Clinical Study on Patients Referred to the National Cancer Research Center for Pap Smears - Alwan, Nada A.S.; Alabbody, Huda Hameed; Yaseen, Safana A.S. (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Cervical cancer ranks the fourth most common cancer among women worldwide and the eighth cancer overall. It is considered as one of the most preventable malignancies, and can be controlled through screening and Pap smears. Objectives: To explore the demographic and clinical characteristics of a sample of Iraqi patients who were referred to the National Cancer Research Center of the University of Baghdad for Pap smear test. Patients and methods: The study enrolled 175 female participants who were subjected to clinical examination and Pap smear tests. A questionnaire was filled for each patient on which demographic and clinical variables were recorded. Cellular specimens were collected, fixed, stained by Papanicolaou stain and examined cytologically. The corresponding cytological findings were correlated with the studied variables and tabulated accordingly. Results: 60% of the 175 women were housewives, 40% got married before the age of 20 years, 35.4% had used contraceptive pills and 10.3% were nulliparous. The mean ages at marriage, pregnancy and first child birth were 20.2, 22.0 and 23.0 years respectively. On clinical examination, cervical erosions were obviously apparent in 41.7% of the cases and genital warts were noted in only one case (0.6%), while koilocytotic cellular atypia was observed in 4.0%. Pap smears revealed infections with Moniliasis and Trichomonas Vaginalis in 16.5% and 1.1% respectively. Atypical metaplastic changes, AGUS (atypical glandular cells of uncertain significance) and ASCUS (atypical squamous cells of undetermined significance) were displayed in 21.1%, 5.7% and 22.3% respectively. Diagnoses of CIN I (LSIL) (cervical squamous intraepithelial neoplasia 1 - low-grade squamous intraepithelial lesion), CIN II and CIN III (HSIL) (high-grade squamous intraepithelial lesion) were reported in 26.8% and 2.3% respectively. Among patients with cervical erosions, the Pap smear findings illustrated more pronounced cellular changes consistent with atypical squamous metaplasia, AGUS and ASCUS (43.8%, 19.2% and 45.2% respectively). On the other hand, LSIL, kiolocytotic atypia and HSIL in these cases were registered in 15.1%, 6.8% and 1.3% respectively. Conclusions: The demonstrated young ages at marriage, pregnancy and childbirth of the examined patients, reflecting the early onset of sexual reproductive activities, and the associated cellular changes urge the necessity for promoting public awareness on the significance of Pap smear screening among Iraqi females. The Bethesda system facilitates easier interpretation of the results; thus fostering the communications between the examining pathologists and the gynecologists.